PENGEMBANGAN USAHA UMKM DODOL PULUT WIZZA MELALUI PENINGKATAN KAPASITAS PRODUKSI, INOVASI PRODUK DAN PENGEMASAN - Komariyah, Siti; Alham, Fiddini; Marnita, Yenni; Gustiana, Cut (Universitas Mataram, 2024)
Dodol Wizza is an MSME (micro, small and medium enterprise) which is engaged in making original dodol pulut (sticky rice). This MSME has several problems, including limited production frequency, products that do not vary and packaging that is less effective. For this problem, the service team provided a solution as an effort to develop Dodol Pulut Wizza MSMEs. The solutions offered to partners include a program to increase production frequency through the procurement of small capacity dodol making pans, as well as product and packaging innovation. From the two programs offered as a solution to partner problems, partners are now producing dodol at least once a month, whereas previously it was only once or twice a year. Mitra also has two variants of dodol, namely original dodol and sesame dodol as well as two packaging variations, namely 500 g packaging priced at 35 thousand rupiah and ready-to-eat packaging priced at 15 thousand rupiah.